2005
DOI: 10.1097/00001756-200507130-00004
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted white matter tract integrity of anterior cingulate in trauma survivors

Abstract: The objective of this study was to examine the integrity of whole-brain white matter in posttraumatic stress disorder patients. Twenty posttraumatic stress disorder patients who survived the Taegu subway fire incident and 20 healthy volunteers participated in this study. Statistical parametric mapping was used to evaluate the global differences in fractional anisotropy values between the two groups. The results show that posttraumatic stress disorder patients had significantly lower fractional anisotropy value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 19 publications
11
61
1
Order By: Relevance
“…In contrast, previous studies have reported decreased cingulum FA of PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011). These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, previous studies have reported decreased cingulum FA of PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011). These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls.…”
Section: Discussionmentioning
confidence: 72%
“…FA is a measure sensitive to alterations in axonal directionality and white matter organization (Beaulieu, 2009). Reduced FA in the cingulum bundle has frequently been reported in PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011), although heightened FA in the cingulum bundle has also been reported (Abe et al, 2006;Zhang et al, 2012). One longitudinal study has investigated white matter microstructure in a small sample of only eight PTSD patients, 10 and 24 months after experiencing a traumatic event ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, according to the quantitative meta-analysis by Daniels and colleagues 18 on whole-brain DTI studies, PTSD was associated with both increased and decreased FA at different locations in the left superior longitudinal fasciculus and at different locations in the bilateral cingulum. These mixed findings may be due to different study designs: patients with PTSD were compared with trauma-exposed 14,[19][20][21] or non-trauma-exposed [22][23][24] controls, although trauma-exposure has been found to alter tract integrity. 25 Additionally, both male and female patients have been included in the same studies, 19,[22][23][24] without specifically investigating or accounting for possible differential effects of sex on tract integrity.…”
Section: J Psychiatry Neurosci 2017;42(5)mentioning
confidence: 99%
“…These mixed findings may be due to different study designs: patients with PTSD were compared with trauma-exposed 14,[19][20][21] or non-trauma-exposed [22][23][24] controls, although trauma-exposure has been found to alter tract integrity. 25 Additionally, both male and female patients have been included in the same studies, 19,[22][23][24] without specifically investigating or accounting for possible differential effects of sex on tract integrity. 26 Therefore, in the present study, we investigated the integrity of several candidate major white matter tracts (i.e., uncinate fasciculus, cingulum bundle, and temporal and parietal projections of the superior longitudinal fasciculus) in patients with PTSD compared with trauma-exposed controls, including both male and female participants to account for potential sex differences.…”
Section: J Psychiatry Neurosci 2017;42(5)mentioning
confidence: 99%
“…Thus, an important line of inquiry is whether individuals with PTSD show changes in ERN amplitude. This is particularly salient in light of the structural and functional alterations in MFC observed in this disorder (Hamner et al, 1999;Shin et al, 2001;Rauch et al, 2003;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 97%